Effectiveness of extracorporeal shock wave therapy for tennis elbow (lateral epicondylitis). Issue 3 (23rd February 2005) - Stasinopoulos, D; Johnson, M I
Abstract : Randomised controlled trials were reviewed to evaluate the evidence of the effectiveness of extracorporeal shock wave therapy in the management of tennis elbow. Seven relevant trials were found, which had satisfactory methodology but conflicting results. Further research with well designed randomised control trials is needed to establish the absolute and relative effectiveness of this intervention for tennis elbow.